2022
DOI: 10.3389/fmed.2021.781287
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing Reveals a Mixed Picture of SARS-CoV-2 Variant of Concern Circulation in Eastern Uttar Pradesh, India

Abstract: Uttar Pradesh is the densely populated state of India and is the sixth highest COVID-19 affected state with 22,904 deaths recorded on November 12, 2021. Whole-genome sequencing (WGS) is being used as a potential approach to investigate genomic evolution of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. In this study, a total of 87 SARS-CoV-2 genomes−49 genomes from the first wave (March 2020 to February 2021) and 38 genomes from the second wave (March 2021 to July 2021) from Eastern Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…No. clade variants mostly the Delta and its variant Delta AY.1 and Kappa (17). Neutralization studies have also substantiated the shift of the Omicron variant as a dominant strain replacing the Delta variant (21).…”
Section: Omicron Variantmentioning
confidence: 89%
See 1 more Smart Citation
“…No. clade variants mostly the Delta and its variant Delta AY.1 and Kappa (17). Neutralization studies have also substantiated the shift of the Omicron variant as a dominant strain replacing the Delta variant (21).…”
Section: Omicron Variantmentioning
confidence: 89%
“…Besides the curfew, other COVID-related protocols and restrictions were also implemented, including bans on gatherings of more than 200 people, cultural and religious events, etc. 1 A previous study from eastern UP has provided comprehensive information on SARS-CoV-2 variants and distinct lineage/clades in the first and second waves ( 17 ). Existing research on the clinical and genomic characteristics of Omicron cases is limited in India ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The center is functioning as one of the nodal centers for COVID‐19 testing in the region of eastern Uttar Pradesh, India. It was on April 8, 2021, when India witnessed the second wave of COVID‐19 due to the Delta variant, 2 we received a message from a laboratory official in the group stating that “I have been tested positive for COVID‐19; all the staff should get tested!” The official was in contact with almost all of the staff working in the laboratory which was one of the COVID‐19 testing centers, which created a fearful situation. But, somewhat we were all consoled by the fact that we all have had received at least one dose of COVID‐19 vaccine shot of ChAdOx1 nCoV‐19 (correspondingly in Kaur et al, 41% had received a single shot and 19% had received both shots of vaccine) in view of the initiatives taken up by the Government of India.…”
mentioning
confidence: 99%
“…This latter vibration is ∼20% lower in the Delta variant than in the Kappa one. A comparison of key residues in SARS-CoV-2 variants by Deval et al 48 significantly lower wavenumber (i.e., 959 cm −1 ) as a consequence of the different structure of the ring. 51,52 On the other hand, a cumulative signal from C−N stretching in both five-membered imidazole and six-membered pyrimidine rings of the adenine (A) purine is displayed at 1150 cm −1 .…”
Section: ■ Resultsmentioning
confidence: 98%
“…This latter vibration is ∼20% lower in the Delta variant than in the Kappa one. A comparison of key residues in SARS-CoV-2 variants by Deval et al has shown that tryptophan was the most common residue in both Delta and Kappa variants. This notion was confirmed by the Raman data shown in this study in comparison with the spectra of two Alpha sub-variants shown in a previously published work …”
Section: Resultsmentioning
confidence: 99%